Pembakaran Terfluidisasi Batubara dengan Menggunakan Campuran LPG-Udara. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
Coal is non renewable fuel that must be used efficiently. Efficiency could be done by good combustion process, which is shown by its high temperature and low emission of Carbon Monoxide. This research was to find Inflammability Limit of combustion of coal, LPG and air, surface reaction constant of heterogeneous reaction of coal with air. Experiment was conducted in fluidization column with 7 cm diameter and 60 cm height. Coal was fed to fluidization column then followed continuously by air and LPG as a fluidization media. The flow rates were varied from minimum fluidization velocity to terminal fluidization velocity. Variables investigated were coal diameter (0.125 mm, 0.250 mm and 0.595 mm), debit of LPG and air entering fluidization column between 420 mL/sec. to 1600 mL/sec. Observed variables are flame height, composition of CO, CO2 and excess 02 product of combustion, temperature of upper section offluidization column and temperature offluidization zone. The observed Lower Inflammability Limit and Upper Inflammability Limit of coal, LPG and air system are 1.036% and 13.655%. Generally, if LPG to air ratio is high the emission of CO is low, CO2 is relatively high and 02 excess is relatively low. Correlation between surface reaction rate constant and temperature can be expressed as k, =1.09 109 e-15132ff cm/s, with the average deviation 7.58%.